2020
DOI: 10.1021/acs.jafc.0c03832
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric Fluorescent Probe Based on Diazotization-Coupling Reaction for Determination of Clenbuterol

Abstract: In view of the potential harm caused by illegal feeding of clenbuterol (CLB) in the livestock industry, herein, a novel ratiometric fluorescent probe based on graphene quantum dots (GQDs)@[Ru(bpy) 3 ] 2+ was elaborately constructed for CLB detection. In this probe, GQDs acted as response signals, and their fluorescence was remarkably quenched by CLB through the diazotization-coupling reaction. As for [Ru(bpy) 3 ] 2+ as a reference signal, its fluorescence was hardly affected. The intensity ratio of two fluorop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Liu et al found that the fluorescence of GQDs could be quenched by CLB through the diazotization-coupling reaction. The decrease in fluorescence intensity was explained by the change in the absorption spectrum of GQDs after the addition of CLB to the diazotization reaction, and the quenching mechanism was investigated by the change in fluorescence lifetime before and after the addition of CLB [43]. We measured the fluorescence lifetime of the N-GQDs solution before and after the addition of CLB (50 µL, 10 −5 M), and the test instrument was Edinburgh FLS 1000, as seen in Figure 4d.…”
Section: Detection For Clb Content In Real Samplesmentioning
confidence: 99%
“…Liu et al found that the fluorescence of GQDs could be quenched by CLB through the diazotization-coupling reaction. The decrease in fluorescence intensity was explained by the change in the absorption spectrum of GQDs after the addition of CLB to the diazotization reaction, and the quenching mechanism was investigated by the change in fluorescence lifetime before and after the addition of CLB [43]. We measured the fluorescence lifetime of the N-GQDs solution before and after the addition of CLB (50 µL, 10 −5 M), and the test instrument was Edinburgh FLS 1000, as seen in Figure 4d.…”
Section: Detection For Clb Content In Real Samplesmentioning
confidence: 99%
“…The detection method showed an LOD of 10 −10 g/ml for clenbuterol. Recently, Liu et al developed a ratiometric GQDs fluorescent probe based on diazotization-coupling reaction for sensitive determination of clenbuterol (Liu et al, 2020). In this sensing probe, GQDs acted as the response signals, and upon the addition of clenbuterol, their fluorescence was remarkably quenched owing to the diazotization-coupling reaction.…”
Section: Livestock Growth Promotersmentioning
confidence: 99%
“…(b) Optical photos of solutions of GQDs (vial 1) and GQDs in the presence of melamine (vial 2) or Hg 2+ (vial 3), and of GQDs-Hg 2+ in the presence of 0.2, 0.8, and 2.0 ppm melamine for vials 4, 5, and 6, respectively, taken under a 365-nm UV lamp (reproduced fromLi et al [2014] with permission from ACS). (iv) Schematic depicting the GQDs@[Ru(bpy) 3 ] 2+ -based ratiometric fluorescent probe for clenbuterol detection (reproduced fromLiu et al [2020] with permission from ACS)…”
mentioning
confidence: 99%
“…Generally, a ratiometric fluorescent probe is a promising tool for naked-eye detection due to reduced environmental interference and distinguished color variations. [33][34][35] Chromophore reaction-based fluorescent probes show distinct colorimetric and ratiometric fluorescent signals by drastic conjugation length changes of chromophores. 36,37 For instance, the core of BODIPY, pyrrolopyrrole aza-BODIPY (PPAB), and pyrrolopyrrole cyanine (PPCy) was susceptible to being attacked by nucleophiles such as a base, hydrazine, and organic amine.…”
Section: Introductionmentioning
confidence: 99%